Identifying Health Systems Gaps as Perceived by Postpartum Patient Navigators at an Urban Academic Medical Center - Hannah M. Green; Maya Daiter; Viridiana Carmona-Barrera; Laura Diaz; Brittney Williams; Ka’Derricka Davis; Joe Feinglass; Arjeme Cavens; Charlotte Nizik; Brigid M. Dolan; Michelle A. Kominiarek; William A. Grobman; et al. (Women's Health Reports)
Background: Although the postpartum period is an opportunity to promote long-term well-being and health systems usage, system complexities limit patients’ abilities to optimize their longitudinal health. Postpartum patient navigation, an intervention that assists individuals in navigating health systems, is a novel innovation that may mitigate barriers to longitudinal care. Methods: Within a recently completed randomized controlled trial (RCT), we conducted a secondary analysis of interviews with two navigators and a subset (N = 15) of navigated participants to describe gaps in the health care system. Semi-structured interview guides were used to conduct 11 sets of interviews with postpartum navigators. In the RCT, navigators supported publicly insured individuals for 1 year postpartum. Interviews focused on relationships with patients and care teams and reflections on health systems gaps which challenged care. Interviews were transcribed and analyzed using grounded theory. A randomly selected subset of interviews with navigated participants was analyzed to triangulate navigator-identified gaps. Results: Navigators identified three major gaps in the care system for postpartum individuals: overall health system challenges, postpartum care challenges, and gaps in the transition to primary care. Health system challenges included fragmentation within the hospital system, fragmentation across distinct health care institutions, high task burden for patients, and lack of clear communication between patients and care teams. Postpartum care challenges included operational and logistical errors in care and the transient nature of obstetric care. Gaps in the transition to primary care included a lack of emphasis on the importance of primary care, lack of administrative support in the transition, and lack of communication between care teams. Conclusions: Postpartum patient navigators elucidated health systems gaps that present challenges in maximizing the longitudinal well-being of birthing individuals. These results identify areas for systems improvements that could promote lifelong health.